The impact of different corneal refractive surgeries on binocular dynamic visual acuity - Wang, Yuexin; Guo, Yining; Li, Yuanting; Zhang, Yu; Yuan, Yifei; Wu, Tingyi; Chen, Yueguo; Li, Xuemin (Frontiers in Neuroscience, 2023)
Purpose: To investigate the influence of different corneal refractive surgeries on dynamic visual acuity (DVA), and explore its potential influence factors. Methods: This was a prospective nonrandomized study. Adult myopic patients undergoing bilateral laser-assisted sub-epithelial keratomileusis (LASEK), femtosecond laser-assisted in situ keratomileusis (FS-LASIK), or small incision lenticule extraction (SMILE) with Plano refraction target were enrolled. Uncorrected and corrected distance visual acuity (UDVA/CDVA), manifest refraction and binocular optotype-moving DVA of 40 and 80 degrees per second (dps) were evaluated preoperatively and postoperatively up to 3 months. Results: The study included 264 eyes of 132 subjects, with an average age of 27.0 ± 6.7 years, and females accounted for 59% of the participants. Significant improvement was observed at the 3-month visit for 40 dps (SMILE, P = 0.001; LASEK, P = 0.006; FS-LASIK, P = 0.010) and 80 dps (SMILE, P = 0.011; LASEK, P = 0.025; FS-LASIK, P = 0.012) DVA. Adjusting for preoperative DVA, there was no significant difference in DVA among groups at 3 months postoperatively (P > 0.05 for multiple comparisons). Overall, multiple linear models demonstrated that postoperative DVA at 3 months was correlated with preoperative DVA (40 dps, β = 0.349, P = 0.001; 80dps, β = 0.447, P < 0.001), preoperative spherical equivalent (40 dps, β = 0.311, P = 0.003; 80 dps, β = 0.261, P = 0.009) and postoperative UDVA (40 dps, β = -0.224, P = 0.024; 80 dps, β= - 0.188, P = 0.05). Conclusion: DVA at 3 months postoperatively of the three corneal refractive surgeries was better than that before the surgery in adult myopic patients, and there was no significant difference among different surgical techniques. Postoperative DVA at 3 months was found correlated with preoperative DVA, preoperative SE, and postoperative UDVA. With further improvement, DVA could be a promising functional visual indicator for myopic patients undergoing refractive surgeries.